Analisis Faktor‐Faktor Penyebab Pelemahan Nilai Tukar Rupiah di Kuartal I 2025 - Ashabi Witjaksono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the first quarter of 2025, the Indonesian rupiah experienced a significant depreciation, weakening from approximately IDR 15,800 per USD in January to IDR 17,200 per USD by the end of March 2025. This study aims to identify and analyze the external and domestic factors contributing to the rupiah’s decline during this period. External pressure mainly stemmed from the U.S. Federal Reserve’s hawkish stance—maintaining its benchmark interest rate at 5.25%–5.50% which triggered capital outflows from emerging markets. Additionally, global geopolitical uncertainty, including tensions in Eastern Europe and trade frictions between the U.S. and China, raised the global risk premium and strengthened the U.S. dollar against the rupiah. On the domestic side, Indonesia’s trade deficit widened to USD 3.2 billion in Q1 2025 due to rising energy import demand amid surging global oil prices. Furthermore, the state budget deficit increased to IDR 104.2 trillion by March 2025 up 20% year on year undermining investor confidence. Using a qualitative descriptive method through content analysis of reports from Bank Indonesia, BPS trade statistics, and relevant media sources, this study finds that the combination of elevated U.S. interest rates, geopolitical tensions, trade imbalances, and fiscal deficits accelerated the depreciation of the rupiah. Policy recommendations include targeted foreign exchange intervention by Bank Indonesia, monetary tightening in line with global trends, fiscal consolidation to reduce the budget deficit, and export diversification to mitigate external shocks.